2010
DOI: 10.1590/s1678-77572010000200007
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of skeletal, dentoalveolar and soft tissue characteristics in white and black Brazilian subjects

Abstract: ObjectiveThis study aimed to compare skeletal, dentoalveolar and soft tissue characteristics in white and black Brazilian subjects presenting normal occlusions.Material and MethodsThe sample comprised the lateral cephalograms of 106 untreated Brazilian subjects with normal occlusion, divided into two groups: Group 1- 50 white subjects (25 of each gender), at a mean age of 13.17 years (standard deviation 1.07); and Group 2- 56 black subjects (28 of each gender), at a mean age of 13.24 years (standard deviation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
1
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 18 publications
(59 reference statements)
7
40
1
12
Order By: Relevance
“…The difference was attributed to the early maturation of girls and their increased nose growth compared to boys. Freitas et al 19 also found different results in white Brazilians with normal occlusion (E-LS = -4.23mm), and although a sample of adolescents was used, the results were similar to those found in this study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The difference was attributed to the early maturation of girls and their increased nose growth compared to boys. Freitas et al 19 also found different results in white Brazilians with normal occlusion (E-LS = -4.23mm), and although a sample of adolescents was used, the results were similar to those found in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Nobuyasu et al 20 in evaluating Brazilian individuals aged between 12 and 15 years with normal occlusion also found more protruded lower lips (-0.95mm ± 2,37mm). Freitas et al 19 found -1.96mm for E-LI in white Brazilian adolescents with normal occlusion. However, the nose and chin positions were not evaluated separately, and those with a more developed nose and chin can provide a good aesthetic appearance due to their greater labial protrusion 21 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Os padrões de crescimento craniofacial variam de acordo com a idade, o sexo e a raça (Siqueira et al, 1999;Patil;Mody, 2005;Beugre et al, 2007;Veyre-Gouletet al, 2008;De Freitas et al, 2010;Gu et al, 2011;Janson et al, 2011;Vela et al, 2011;Yadav et al, 2011).…”
Section: Avaliação Do Crescimento E Desenvolvimento Através Da Morfolunclassified